Reduction-Hypersensitive Podophyllotoxin Prodrug Self-Assembled Nanoparticles for Cancer Treatment - Xinhui Wang; Yuequan Wang; Jiaxin Yu; Qian Qiu; Rui Liao; Shenwu Zhang; Cong Luo (MDPI AG, 2023)
Podophyllotoxin (PPT) has shown strong antitumor effects on various types of cancers. However, the non-specific toxicity and poor solubility severely limits its clinical transformation. In order to overcome the adverse properties of PPT and explore its clinical potential, three novel PTT−fluorene methanol prodrugs linked by different lengths of disulfide bonds were designed and synthesized. Interestingly, the lengths of the disulfide bond affected the drug release, cytotoxicity, pharmacokinetic characteristics, in vivo biodistribution and antitumor efficacy of prodrug NPs. To be more specific, all three PPT prodrugs could self-assemble into uniform nanoparticles (NPs) with high drug loading (>40%) via the one-step nano precipitation method, which not only avoids the use of surfactants and cosurfactants, but also reduces the systemic toxicity of PPT and increases the tolerated dose. Among the three prodrug NPs, FAP NPs containing α-disulfide bond showed the most sensitive tumor-specific response and fastest drug release rate, thus demonstrating the strongest in vitro cytotoxicity. In addition, three prodrug NPs showed prolonged blood circulation and higher tumor accumulation. Finally, FAP NPs demonstrated the strongest in vivo antitumor activity. Our work will advance the pace of podophyllotoxin towards clinical cancer treatment.